Efektivitas Pemberian Daun Ubi Jalar Terhadap Penurunan Involusi Uteri Pada Ibu Nifas - Montolalu, Agnes; Keintjem, Femmy; Limbengpiah, Sani Erawati; Kuhu, Fonnie; Donsu, Amelia; Manueke, Iyam; Lontaan, Anita; Adam, Yulin; Lumy, Freike SN.; Solang, Sesca D. (JIDAN Jurnal Ilmiah Bidan, 2023)
Background : Uterine involution during the puerperium must go well so efforts are needed to accelerate uterine involution, one of which is consuming sweet potato leaves. Sweet potato leaves have nutrients that can help mothers reduce involution more quickly, and can also increase milk production. An increase in the hormone oxytocin can reduce the height of the uterine fundus. Objective : Knowing the effect of giving sweet potato leaves to reduce uterine involution in postpartum women at the Sifra Langowan maternity clinic. Methods : This research usesQuasi-experimental design with a plan one-group pretest – posttest design. The sample of this research was postpartum mothers from the 1st to the 7th day as many as 15 respondents, determined by means purposive sampling. Data was collected using an observation sheet which contained a number of indicators for evaluating decreased uterine involution in writing which were filled in before and after the intervention was given. Data analysis used the Paired Sample T-Test. Results : Test results Paired sample T-Test There is an effect of sweet potato leaves on reducing uterine involution in postpartum women at the Sifra Langowan maternity clinic. recommendations for postpartum mothers to consume sweet potato leaves regularly during the postpartum period to help reduce uterine involution